(untitled) (Fiep Bulletin - online, 2013)
Introduction: A pedometer is an economically accessible movement sensor, capable of quantifying the number of steps taken by an individual. They are useful not only for evaluation but also as an incentive to the usual practice of physical activity. There are several available publications about pedometers nevertheless, there are still aspects not fully defined, e.g., the influence factors such as the user’s body mass index (BMI) and the kind of trajectory in which the subject walks (flat ground, stairs, inclined ramp, curves). Objectives: To study the influence of different trajectories and body mass index (BMI) on the accuracy of step detection by a pedometer. Methods: One-hundred healthy subjects from both genders, 18 to 59 years, were divided in three groups according to their BMI: eutrophic (EU; n=40); overweight (OW; n=30) and obese (OB; n=30). While wearing one pedometer Yamax Digiwalker SW-701 placed at the right side of the waist, the subject walked 50 steps at usual speed in six different trajectories: straight line and walking in curves (or “zigzag”) on the level, ascending and descending ramps, upstairs and downstairs. Results: As for the BMI, OB showed significant underestimation compared to EU and OW (p<0.05 for both). Accuracy was similar and acceptable (error <5%) in the different trajectories except for the “zigzag”, which showed lower number of steps detected in comparison to the others (p<0.05). Although modestly, the factor which showed higher correlation with the accuracy in all trajectories was the BMI (r = -0.41; p<0.0001). Conclusions: The accuracy of the Yamax Digiwalker SW-701 pedometer in obese subjects walking at their usual speed is low and negatively related to the BMI. Furthermore, walking in curvilinear trajectory decreases the pedometer accuracy in all subjects, regardless of the BMI.